Advances in multi-omics integrated analysis methods based on the gut microbiome and their applications - Duan, Dongdong; Wang, Mingyu; Han, Jinyi; Li, Mengyu; Wang, Zhenyu; Zhou, Shenping; Xin, Wenshui; Li, Xinjian (Frontiers in Microbiology, 2025)
The gut microbiota actually shares the host’s physical space and affects the host’s physiological functions and health indicators through a complex network of interactions with the host. However, its role as a determinant of host health and disease is often underestimated. With the emergence of new technologies including next-generation sequencing (NGS) and advanced techniques such as microbial community sequencing, people have begun to explore the interaction mechanisms between microorganisms and hosts at various omics levels such as genomics, transcriptomics, metabolomics, and proteomics. With the enrichment of multi-omics integrated analysis methods based on the microbiome, an increasing number of complex statistical analysis methods have also been proposed. In this review, we summarized the multi-omics research analysis methods currently used to study the interaction between the microbiome and the host. We analyzed the advantages and limitations of various methods and briefly introduced their application progress.